STRATEGI DISPERINDAGKOP UKM DI PEMERINTAH KABUPATEN/KOTA DALAM PENGEMBANGAN HOME INDUSTRY DI INDONESIA - Nanik Pujiastuti Dan Frendly Albertus (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
The purpose of the Indonesian state is as stated in the Preamble of the 1945 Constitution of the fourth paragraph: "To protect the whole nation of Indonesia and the entire blood of Indonesia, to promote the common good, to educate the life of the nation, and to carry out the world order based on freedom, eternal peace and social justice" . Executor of home industry development strategy in every District Government in Indonesia is based on Regulation of Minister of Cooperative and UKM. 06 of 2012 on the description of the main duties and function of structural positions in each SKPD in charge of the Cooperative and SMEs of the Regency and the City, the District and Municipal Government have the duty to assist the Central Government in exercising authority in the field of Industry, Trade, Cooperatives and SMEs based on the principle of autonomy And co-administration tasks. Included in the home industry development. In the implementation of home industry development strategy, there are supporting factors such as and good cooperation between the Central Government with the District and City Government as well as supporters such as institutions, banking institutions and other relevant practitioners, as well as a harmonious relationship with small entrepreneurs. There is also the factor inhibitors, such as, internal factor of Regency / City Government is the level of quality and quantity of apparatus is still limited, the amount of budget funds for the development of SMEs. As well as facilities and infrastructure are still inadequate. External inhibiting factors are the level of human resource quality is still limited, lack of entrepreneurial interest (no regeneration), high production prices whereas low purchasing power, handicraft and snack foods are still monotonous, as well as security conditions and unfavorable political situation.